2009
DOI: 10.1089/hum.2009.103
|View full text |Cite
|
Sign up to set email alerts
|

Safety Evaluation of AAV2-GDNF Gene Transfer into the Dopaminergic Nigrostriatal Pathway in Aged and Parkinsonian Rhesus Monkeys

Abstract: We evaluated neuropathological findings in two studies of AAV2-GDNF efficacy and safety in naive aged (>20 years) or MPTP (1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine)-lesioned rhesus macaques. In the first study, a total of 17 animals received one of two doses of AAV2-GDNF into either putamen or substantia nigra (SN). To control for surgical variables, all animals received identical putaminal and nigral infusions in which phosphate-buffered saline was substituted for vector as appropriate. All 17 aged monkey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
82
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(90 citation statements)
references
References 35 publications
(45 reference statements)
7
82
1
Order By: Relevance
“…3b and c), consistent with previous reports demonstrating slight inflammation after CED from a stepped cannula (Su et al, 2009). In all animals, areas of both caudate nucleus and putamen 0.75 mm away from the infusion site were not considered positive by H&E staining, or by GFAP and Iba1 staining, because they exhibited basal expression of these markers.…”
Section: Performance Of Delivery Platform and Cannulasupporting
confidence: 89%
“…3b and c), consistent with previous reports demonstrating slight inflammation after CED from a stepped cannula (Su et al, 2009). In all animals, areas of both caudate nucleus and putamen 0.75 mm away from the infusion site were not considered positive by H&E staining, or by GFAP and Iba1 staining, because they exhibited basal expression of these markers.…”
Section: Performance Of Delivery Platform and Cannulasupporting
confidence: 89%
“…Specifically, no problems were encountered with respect to stereotactically targeting the SNc, expression of a trophic factor in the SNc, or possible spread to adjacent sites like the ventral tegmental area or hypothalamus. More specifically, we did not observe weight loss, which has been reported as a potential concern for targeting the SN with neurotrophic factors, based on certain preclinical studies, 5,6,11 though others suggested that outcome is likely due to mistargeting protein extending into the ventricles or hypothalamus. 9 We also did not observe any evidence of psychiatric symptoms such as addiction or psychosis that theoretically might result from trophic enhancement of the ventral tegmental area.…”
Section: 10contrasting
confidence: 48%
“…However, a number of safety concerns have been raised regarding stereotactically targeting the SNc and expressing neurotrophic factors in the substantia nigra (SN) and surrounding structures. [4][5][6] Based on safety associated with targeting the SNc and neighboring regions in patients with PD with deep brain stimulation 7 and fetal tissue transplant, 8 and the lack of serious side effects observed following NRTN gene delivery to the SNc in preclinical studies, 9 we began a clinical trial in patients with advanced PD. In the present article, we present the 24-month results of an open-label safety study of 6 patients who underwent bilateral NRTN gene delivery (CERE-120) to the putamen and SNc.…”
mentioning
confidence: 99%
“…Further study between the relationship of GDNF administration and functional recovery indicates a role for GDNF in modulating dopamine plasticity in the striatum. Safety and efficacy studies in non-human primates demonstrated that the injections do not cause any negative histological effects in the injected brain and that the most notable side effect of GDNF delivery was weight loss (Su et al, 2009). These studies advanced the field towards using GDNF in human clinical trials.…”
Section: Glial Cell-line Derived Neurotrophic Factormentioning
confidence: 92%